Reliability of functional gait assessment in patients with Parkinson disease: Interrater and intrarater reliability and internal consistency. Issue 34 (August 2016) - Yang, Yaqin; Wang, Yongjun; Zhou, Yanan; Chen, Chen; Xing, Deli
Abstract : Abstract: To determine the reliability of the functional gait assessment (FGA) as a measure of balance and gait in patients with Parkinson disease (PD). This study involved121 inpatients with PD (mean age 61.9 years). The participants were scored using the FGA by 2 raters, and the testing procedure was videotaped. One of the raters re-assessed the same FGA test via review of the videotaped test 4 weeks later. The interrater and intrarater reliability of the total FGA score was found to be excellent, with an intraclass correlation coefficient of 0.99. The reliability of single items of the FGA ranged from 0.49 to 0.99. The internal consistency of the FGA scores was 0.94. The FGA has high inter-rater and intrarater reliability, and internal consistency for evaluating balance and gait disorders in patients with PD.